STEM Students’ Motivation, Interest, and Career Direction Amid New Normal Education: A Narrative Inquiry Research - Manalo, Franz Kevin (SEAQIS Journal of Science Education, 2024)
The abrupt transition of learning modalities and the global health crisis brought by the COVID-19 pandemic have reshaped the learners’ experiences and insights, particularly in STEM (Science, Technology, Engineering, and Mathematics) education. Hence, this study was conducted to explore the stories of senior high school STEM learners on how the new normal education impacted their motivation, interest, and career direction using a narrative inquiry research design. Purposive sampling was used to select twelve participants from a public senior high school offering the STEM strand. A Semi-structured interview guide, which underwent expert judgment, was used to collect data. After securing consent forms, in-depth interviews were conducted via online platforms. Data collected were transcribed, coded, categorised, and thematised, applying Polkinghorne’s analysis of narratives. Results illustrated that students’ (a) motivation has declined, causing discouragement in STEM activities, however, their passion and goals kept them eager; (b) interest was elevated by their constant commitment to STEM endeavours, yet less enthusiasm has become evident; (c) career direction was still definite as fuelled by relevance, though some have restructured theirs due to the drastic change of circumstances. Furthermore, students devised adaptive strategies to further enrich themselves in STEM undertakings such as improving STEM identity, fostering STEM competence and habits, reorganisation of tasks, and peer collaboration. The findings of this study led to the creation of an action plan to further improve the STEM learning experiences of students amid the radical educational change. This research employed a holistic perspective as it considers the nature, aspect, and meaning of students’ narratives.